ANALISIS YURIDIS TERHADAP PEMBATALAN AKTA SURAT KUASA YANG DIBUAT DENGAN AKTA NOTARIS TERKAIT DENGAN PERALIHAN HAK YANG OBJEKNYA DALAM JAMINAN BANK (STUDI PUTUSAN No. 445/PDT-G/2015/PN.Mdn Jo No. 49/Pdt/2017/PT.Mdn) - Rio Rinchy Siahaan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
Decision on Case Number: 49/PDT/2017/PT.Medan which is an examination of the appeal level of Decision on Case Number 445/Pdt.G/2015/PN.Medan. The Panel of Judges carried out a deed of power related to the ownership of Property Rights Certificate Number 1085/Desa Seikambing B. Asmidar Chandry as the power of attorney to sue Zainurah (recipient of power of attorney), Head of the Land Office, and Notary/PPAT at the Medan District Court for violating the law. Results Based on the examination at the trial that the power of attorney was made in accordance with the provisions of the legislation. In fact, the power of attorney is made by the power of attorney on the basis of his will. Regarding this case, the problem is: How is the arrangement of the power of attorney made before a notary based on the laws and regulations? What is the accountability of the power of attorney made by a notary without the original document whose object is in his power as bank guarantee? What are the legal consequences for music Deed of power of attorney who listens with copyright? So that this research is entitled